Decision Support Systems to Determine Electronic Sales Products using The TOPSIS Method - Pangaribuan, Andi Pranata; Rita Hamdani (Sean Institute, 2023)
Products are everything that is traded. One of the tradable products is electronic products. One of the shops that sells electronic products in Medan is the Asia Electric Shop. The Asia Electric shop which sells electronic goods such as lamps, electrical appliances, furniture and so on. In fulfilling product stock in the store, order products that match the product category to be sold directly to the factory. This will cause a large stock of products in the warehouse. So that the Asian Electric Shop Owner has not been able to determine the exact electronics sales product. The owner must determine the right product sales and suitable for sale in the market, because the sale of products is part of company management and is also a very important factor that will directly affect the smooth running or confidence of the store in being successful. Therefore we need a